Effect of seed vigor and sowing densities on the yield and physiological potential of wheat seeds - Cardoso, Carolina Pereira [UNESP]; Bizzarri Bazzo, Jose Henrique; Marinho, Jessica de Lucena; Zucareli, Claudemir (Abrates-assoc Brasileira Technologia Sementes, 2021)
Initial seed vigor and sowing density interact in establishment of plants in the field, and can thus affect expression of the plasticity of the wheat crop and the yield and physiological quality of the seeds produced. The aim of this study was to evaluate the effect of seed vigor levels in combination with sowing densities on the yield and physiological potential of wheat seeds. The cultivars BRS Gralha-Azul and BRS Sabia were used in a randomized block experimental design in a 2 x 4 factorial arrangement, with four replications. The treatments consisted of seeds of high and low vigor and four sowing densities (150, 250, 350, and 450 seeds.m(-2)). The following evaluations were made: seed yield, germination, first germination count, seedling length, seedling dry matter, accelerated aging, emergence speed index, and seedling emergence in sand. An increase in sowing density favors the seed yield of both cultivars; however, it reduces the vigor of the seeds produced by the cultivar BRS Gralha-Azul, especially of the seeds produced by plants originating from high vigor seeds. For the cultivar BRS Sabia, an increase in sowing density decreases the germination performance of seeds produced by plants originating from low vigor seeds.
Keywords: Triticum aestivum L.; seed quality; germination; plant population; physiological performance